2016
DOI: 10.1007/s00220-016-2659-y
|View full text |Cite
|
Sign up to set email alerts
|

Wilson Loop Diagrams and Positroids

Abstract: Abstract:In this paper, we study a new application of the positive Grassmannian to Wilson loop diagrams (or MHV diagrams) for scattering amplitudes in N= 4 Super Yang-Mill theory (N = 4 SYM). There has been much interest in studying this theory via the positive Grassmannians using BCFW recursion. This is the first attempt to study MHV diagrams for planar Wilson loop calculations (or planar amplitudes) in terms of positive Grassmannians. We codify Wilson loop diagrams completely in terms of matroids. This allow… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
47
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 9 publications
(48 citation statements)
references
References 16 publications
1
47
0
Order By: Relevance
“…However the WLDs apparently lend themselves very naturally and directly to a geometrical interpretation and in this paper we wish to look again at the relationship between WLDs and the amplituhedron. Previous work also examining this connection includes [9,18,26]. In particular in [26] it was shown that the WLDs give a very natural description of the physical boundary of the amplituhedron.…”
Section: Introductionmentioning
confidence: 99%
“…However the WLDs apparently lend themselves very naturally and directly to a geometrical interpretation and in this paper we wish to look again at the relationship between WLDs and the amplituhedron. Previous work also examining this connection includes [9,18,26]. In particular in [26] it was shown that the WLDs give a very natural description of the physical boundary of the amplituhedron.…”
Section: Introductionmentioning
confidence: 99%
“…Every element of (∅) defines a circuit of size 1, and all other circuits of ( ) must contain at least two elements. In this section we develop this analysis further, showing the converse of this result from [5] (see Theorem 3.19). We also enumerate the number of diagrams that map to a particular matroid in Corollary 3.20.…”
Section: Remark 28mentioning
confidence: 83%
“…There are a few things to note here. First, what we call weakly admissible here is called admissible in ( [5], see definition 1.11 and section 1.3). Note also that if two propagators have the same pair of supporting edges, or if a propagator is supported on two adjacent edges, then the Wilson loop diagram is not admissible or even weakly admissible.…”
Section: Definition 24 a Wilson Loop Diagrammentioning
confidence: 99%
See 2 more Smart Citations